2015
DOI: 10.1186/1472-684x-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Initial development and psychometric testing of an instrument to measure the quality of children’s end-of-life care

Abstract: BackgroundThe field of pediatric palliative care is hindered by the lack of a well-defined, reliable, and valid method for measuring the quality of end-of-life care.MethodsThe study purpose was to develop and test an instrument to measure mothers’ perspectives on the quality of care received before, at the time of, and following a child’s death. In Phase 1, key components of quality end-of-life care for children were synthesized through a comprehensive review of research literature. These key components were v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 37 publications
2
64
1
2
Order By: Relevance
“…Interviewees also reiterated and elaborated on other key findings from Xafis et al [26], such as a general lack of availability of resources of this type, the usefulness of providing parents with a language that could facilitate further communication, and a perception that ascertaining the right time to distribute or make parents aware of the resource is delicate and, if not done well, could present some difficulties. Parents have also expressed the view that such information should only be provided when parents are ready to receive it [50].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Interviewees also reiterated and elaborated on other key findings from Xafis et al [26], such as a general lack of availability of resources of this type, the usefulness of providing parents with a language that could facilitate further communication, and a perception that ascertaining the right time to distribute or make parents aware of the resource is delicate and, if not done well, could present some difficulties. Parents have also expressed the view that such information should only be provided when parents are ready to receive it [50].…”
Section: Discussionmentioning
confidence: 92%
“…The use of written materials enables families to access language and concepts [24, 25] and can provide one potential way of building decision-making literacy in families [26]. Provision of written informational materials encouragesing parents to speak with each other and participate in otherwise clinically-dominated decision-making environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear if these tools are applicable to the specific illness trajectory experienced by people with a hematological malignancy [68]. A number of studies exist highlighting key prognostic factors in the final months of life for people with a solid tumor diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument shows promise for the retrospective application in bereaved mothers. However, the applicability in bereaved fathers remains an open question (Widger et al 2015).None of the instruments available at the beginning of this study included all of the quality domains identified by the IPPC and were applicable to the heterogeneous field of paediatric EOL care, including children/adolescents of different age groups, with different underlying illnesses and in different clinical settings and finally, none considered maternal and paternal perspectives. Gaining uniform information across these different situations will help identifying differences between subgroups and thus, add important and essential knowledge needed for healthcare professionals to provide individualized family-centred care during this difficult period of time.…”
mentioning
confidence: 97%